Evaluating Burkholderia pseudomallei Bip proteins as vaccines and Bip antibodies as detection agents - Chris Druar (2018)
Burkholderia pseudomallei is a biothreat agent and an important natural pathogen, causing melioidosis in humans and animals. A type III secretion system (TTSS-3) has been shown to be critical for virulence. Because TTSS components from other pathogens have been used successfully as diagnostic agents and as experimental vaccines, it was investigated whether this was the case for BipB, BipC and BipD, components of B. pseudomallei's TTSS-3. The sequences of BipB, BipC and BipD were found to be highly conserved among B. pseudomallei and B. mallei isolates. A collection of monoclonal antibodies (mAbs) specific for each Bip protein was obtained. Most recognized both native and denatured Bip protein. Burkholderia pseudomallei or B. mallei did not express detectable BipB or BipD under the growth conditions used. However, anti-BipD mAbs did recognize the TTSS needle structures of a Shigella strain engineered to express BipD. The authors did not find that BipB, BipC or BipD are protective antigens because vaccination of mice with any single protein did not result in protection against experimental melioidosis. Enzyme-linked immunosorbent assay (ELISA) studies showed that human melioidosis patients had antibodies to BipB and BipD. However, these ELISAs had low diagnostic accuracy in endemic regions, possibly due to previous patient exposure to B. pseudomallei. © 2007 Camgene Corporation.